Endocytoscopic observation of various esophageal lesions at ×600: can nuclear abnormality be recognized?. Issue 3 (28th January 2014) - Kumagai, Y.; Kawada, K.; Higashi, M.; Ishiguro, T.; Sobajima, J.; Fukuchi, M.; Ishibashi, K.; Baba, H.; Mochiki, E.; Aida, J.; Kawano, T.; Ishida, H.; et al.
Summary Endocytoscopy (ECS) is a novel endoscopic technique that allows detailed diagnostic examination of the gastrointestinal tract at the cellular level. We previously reported that use of ECS at ×380 magnification (GIF‐Y0002) allowed a pathologist to diagnose esophageal squamous cell carcinoma (ESCC) with high sensitivity (94.9%) but considerably low specificity (46.7%) because this low magnification did not reveal information about nuclear abnormality. In the present study, we used the same magnifying endoscope to observe various esophageal lesions, but employed digital 1.6‐fold magnification to achieve an effective magnification of ×600, and evaluated whether this improved the diagnostic accuracy in distinguishing neoplastic from non‐neoplastic lesions.We examined the morphology of surface cells using vital staining with toluidine blue and compared the histological features of 40 cases, including 19 case of ESCC and 21 non‐neoplastic esophageal lesions (18 cases of esophagitis, 1 case of glycogenic acanthosis, 1 case of leiomyoma, and 1 case of normal squamous epithelium). One endoscopist classified the lesions using the type classification, and we consulted one pathologist for judgment of the ECS images as 'neoplastic', 'borderline', or 'non‐neoplastic'. At ×600 magnification, the pathologist confirmed that nuclear abnormality became evident, in addition to the information about nuclear density provided by observation at ×380. The overall sensitivity and specificity with which the endoscopist was able to predict neoplastic lesions using the type classification was 100% (19/19) and 90.5% (19/21), respectively, in comparison with values of 94.7% (18/19 cases) and 76.2% (16/21), respectively, for the pathologist using a magnification of ×600. The pathologist diagnosed two non‐neoplastic lesions and one case of ESCC showing an apparent increase of nuclear density with weak nuclear abnormality as 'borderline'. Among the 21 non‐cancerous lesions, two cases of esophagitis that were misdiagnosed by the endoscopist were also misinterpreted as 'neoplastic' by the pathologist. We have shown, by consultation with a pathologist, that an ECS magnification of ×600 (on a 19‐inch monitor) is adequate for recognition of nuclear abnormality. We consider that it is feasible to diagnose esophageal neoplasms on the basis of ECS images, and that biopsy histology can be omitted if a combination of increased nuclear density and nuclear abnormality is observed.